Antiproliferative activity of O4-benzo[c]phenanthridine alkaloids against HCT-116 and HL-60 tumor cells. Issue 14 (15th July 2015) - Hatae, Noriyuki; Fujita, Erina; Shigenobu, Saori; Shimoyama, Sayumi; Ishihara, Yuhsuke; Kurata, Yuhki; Choshi, Tominari; Nishiyama, Takashi; Okada, Chiaki; Hibino, Satoshi
Graphical abstract: Abstract: The O 4 -benzo[ c ]phenanthridine alkaloids exhibit potent antiproliferative activity against cancer cells, which is derived from their ability to inhibit of topoisomerase I and II. It has been reported that in the alkaloids a cationic quaternary ammonium atom, which results in resonance effects between ring A and B, is necessary for increased antiproliferative activity. These findings indicate the role of their substituents at ring A on inhibition of tumor cell proliferation. In the present study, we systematically assessed the cytotoxic activities of naturally occurring alkaloids and their derivatives containing various ring A substituents against two tumor cell lines, HCT-116 colon tumor cells and HL-60 promyelocytic leukemia cells. Among the cationic iminium alkaloids, which displayed more potent activity than the corresponding neutral derivatives, and the 7, 8-oxygenated benzo[ c ]phenanthridine alkaloids, chelerythrine and NK109, exhibited stronger antiproliferative activity than the 8, 9- and 9, 10-oxygenated alkaloids. The activity of cationic iminium alkaloids could be correlated with the bond lengths of their ring A substituents and the electrostatic potentials of their ammonium molecules by DFT calculation.